The Selection of Reagents for Ionic Flotation of Non-Ferrous Metals in the Series of N-Acyl-N'-Mezylhydrazines - Chekanova, L.G.; Vaulina, V.N.; Elchischeva, Yu.B.; Bardina, E.S.; Pavlov, P.T. (Karagandy University of the name of academician E.A. Buketov, 2022)
A series of new ligands — N-acyl-N'-mesylhydrazines (MSH) — of the general formula RC(O)NHNHSO2CH3 has been obtained and considered as reagents for ionic flotation (IF) of non-ferrous metals (M(II). Reagents with a radical length of C6H13 and above form hardly soluble complexes with M(II) so it is possible to implement a kind of the ionic flotation techniques — “precipitate flotation”. The ranges of pH values of the most complete precipitation of cations from solutions have been determined. Precipitates of the metal complexes were isolated; their composition was confirmed by IR spectroscopy and elemental analysis. The conditional values of the solubility product (SP) of the complexes [M(HL)2] were calculated. The dependence –lg SP = 11.8 + 0.61N is fulfilled for the MSH series and Cu(II) ions. The surface-active properties of compounds with R > C6H13 were established. The reagents with optimal radical length for ionic flotation were selected. The ionic flotation of non-ferrous metals with N-nonanoyl-N'-mesylhydrazine was carried out. The up to 95–99 % recovery of metal ions, separation of copper and associated metal ions in diapason of pH 5–6.5 was shown to be possible.
N-ацил-N'-мезилгидразиндер қатарындағы түсті металдардың иондық флотациясына арналған реагенттерді таңдау
Выбор реагентов для ионной флотации цветных металлов в ряду N-ацил-N'-мезилгидразинов
Keywords: ionic flotation; precipitate flotation; sulfonylhydrazines; non-ferrous metals; physico-chemical properties; surface-active substances